2018
DOI: 10.1002/jctb.5848
|View full text |Cite
|
Sign up to set email alerts
|

The use of bioelectrochemical systems in environmental remediation of xenobiotics: a review

Abstract: Remediation of anthropogenic pollutants in our environment has become an imperative of the 21st century in order to sustain human activity and all life on the planet. With the current limitations of the existing technologies for this purpose, the need for innovative bioremediation technologies has become vitally important. Hitherto, electrochemically active microorganisms have only been a scientific curiosity and a platform for sustainable power production from waste material. However, recent research utilizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…However, when used for the purpose of decomposition, the fPFC can provide larger power densities from the degradation of MB (Figure S7, Supporting Information) . The fPFC also provides comparable energy output to microbial cells in the decomposition of other dyes . A comparison of power generation performance using sweat and organic dye fuels can be found in Table S3 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…However, when used for the purpose of decomposition, the fPFC can provide larger power densities from the degradation of MB (Figure S7, Supporting Information) . The fPFC also provides comparable energy output to microbial cells in the decomposition of other dyes . A comparison of power generation performance using sweat and organic dye fuels can be found in Table S3 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…These systems currently are being studied for a wide range of potential applications such as recalcitrant pollutant removal, chemical synthesis, resource recovery and biosensors . For example, reduction of hexavalent chromium, ammonia recovery, remediation of xenobiotics, remediation of toxic metal contaminated soil, sulfate reduction or polishing effluents of anaerobic digesters are some of the applications reported recently for BES. Moreover, the generation of different products such as electricity, hydrogen, methane, biofuels, desalinated water or high‐value chemical products already has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In the design of a remediation activity of a wide polluted area, geophysical surveys are often associated with hydrogeological surveys and drilling and coring campaigns, to assess the hydrology, geology, hydrogeological settings, and the contamination level. Nowadays, the main oil clean-up methodologies refer to bioremediation [2], which exploits the activity of microorganisms or plants 2 of 17 to degrade or accumulate pollutants. A previous laboratory-scale study showed that biostimulated indigenous microorganisms can successfully remove diesel oil from soil [3].…”
Section: Introductionmentioning
confidence: 99%